2022
DOI: 10.1001/jamaoncol.2022.5020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Participation Among Older Adult Medicare Fee-for-Service Beneficiaries With Cancer

Abstract: ImportanceClinical trials play a critical role in the development of novel cancer therapies, and precise estimates of the frequency with which older adult patients with cancer participate in clinical trials are lacking.ObjectiveTo estimate the proportion of older adult Medicare Fee-for-Service (FFS) beneficiaries with cancer who participate in interventional cancer clinical trials, using a novel population-based methodology.Design, Setting, and ParticipantsIn this retrospective cohort study evaluating clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Underrepresentation of diverse racial and ethnic populations in clinical trials is also concerning. In a recent study on Medicare beneficiaries with cancer, only 1% to 1.9% of participants had medical claims for interventional clinical trials, and most participants were younger and a race other than Black …”
mentioning
confidence: 99%
“…Underrepresentation of diverse racial and ethnic populations in clinical trials is also concerning. In a recent study on Medicare beneficiaries with cancer, only 1% to 1.9% of participants had medical claims for interventional clinical trials, and most participants were younger and a race other than Black …”
mentioning
confidence: 99%
“…Therefore, the broader clinical implications of the data may be limited, as trial participants are often not a fair representation of the real-world patient population. Clinical trial participants tend to be younger, fitter, a race other than Black, and residing in zip codes with high median incomes . Consequently, the effect of ARSI therapy on an older, socioeconomically underserved patient population might be even greater than presented by Nowakowska et al…”
mentioning
confidence: 99%
“…Inadequate and skewed enrollment into clinical trials has been recognized for more than 30 years, generating calls for action and policy remedies. In a retrospective cohort study of more than 1 million Medicare beneficiaries in this issue of JAMA Oncology , Green et al report that the crisis in cancer research enrollment continues: fewer than 1 out of every 50 older adults who are undergoing active cancer therapy were enrolled in a clinical trial. They also found substantial disparities by race, age, socioeconomic status, and comorbidity.…”
mentioning
confidence: 99%
“…The study by Green et al also found that fewer than 2% of older adult patients undergoing cancer-directed therapy were enrolled in therapeutic trials. This is a distressingly low number, but not a surprising one.…”
mentioning
confidence: 99%
See 1 more Smart Citation